Factors Affecting the Completeness of Basic Vaccination for Toddlers - Eni Indrayani; Juni Sofiana; Hastin Ika Indriyastuti; Wulan Rahmadhani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Vaccination is an effective way to reduce infant mortality. It can also prevent some infectious diseases and reduce disability rates in infants. Although vaccination has been proven to be a vital public health effort, its coverage has not yet reached the predetermined target of the Ministry of Health's Strategic Plan. Factors influencing mothers’ intention to get their babies vaccinated are education, knowledge, age, support, attitude, and distance. This research aims to analyze factors affecting the completeness of basic vaccination for toddlers. This analytical study used a survey method with a retrospective approach. Data were collected by distributing questionnaires. Data analysis covered univariate and bivariate analyses using the Chi-square. The population in this study was mothers with toddlers aged 12-24 months. The total sampling size was 165 mothers. The results showed that around 160 (97%) mothers completed their toddlers’ basic vaccination, while the other 5 mothers (3%) did not complete their toddlers’ vaccination. Education (p=9.992), occupation (p=9.746), knowledge (p=0.890), support (p=0.764), attitude (p=0.095), and distance (p=2.354) did not influence the completeness of vaccination. However, age (p=0.004) influenced the completeness of basic vaccination for toddlers. It can be concluded that age influences the completeness of basic vaccination for toddlers with a value of (p=0.004).